Growth enhancement and toxic effects of lithium on HL-60 promyelocytic leukaemia cells the involvement of insulin - Teffo, Leah Snow (University of Limpopo, 2001)
Refer to document
Thesis (M.Sc. (Biochemistry))-- University of Limpopo, 2001
Keywords: Lithium; Manic depression; HL-60 promyelocitic leukaemia; Lithium; Leukaemia; Cancer cells; Cell proliferation; Insulin